2015
DOI: 10.1155/2015/617190
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Behavior of Children with ASD toward Pictures of Facial Expressions

Abstract: Atypical gaze behavior in response to a face has been well documented in individuals with autism spectrum disorders (ASDs). Children with ASD appear to differ from typically developing (TD) children in gaze behavior for spoken and dynamic face stimuli but not for nonspeaking, static face stimuli. Furthermore, children with ASD and TD children show a difference in their gaze behavior for certain expressions. However, few studies have examined the relationship between autism severity and gaze behavior toward cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
2
7
0
1
Order By: Relevance
“…This trend supports previous studies which have shown a link between ASD symptoms and social attention towards social stimuli (Bird et al 2011 ; Chawarska et al 2012 ; Klin et al 2002 ). It also supports the efficacy of measuring symptom severity amongst ASD populations given the growing body of research that has found links between differential gaze patterns for ASD children towards different facial expressions depending on autism severity (Matsuda et al 2015 ). The internal consistency demonstrated here between a teacher report of a child’s behaviour (based on classroom observations over past 6 months) and eye-tracking data gathered in a ‘real-world’ setting of a classroom, confirms how eye-tracking data can complement and act as an objective measure to better understand the social behaviour of a child with ASD.…”
Section: Discussionsupporting
confidence: 54%
“…This trend supports previous studies which have shown a link between ASD symptoms and social attention towards social stimuli (Bird et al 2011 ; Chawarska et al 2012 ; Klin et al 2002 ). It also supports the efficacy of measuring symptom severity amongst ASD populations given the growing body of research that has found links between differential gaze patterns for ASD children towards different facial expressions depending on autism severity (Matsuda et al 2015 ). The internal consistency demonstrated here between a teacher report of a child’s behaviour (based on classroom observations over past 6 months) and eye-tracking data gathered in a ‘real-world’ setting of a classroom, confirms how eye-tracking data can complement and act as an objective measure to better understand the social behaviour of a child with ASD.…”
Section: Discussionsupporting
confidence: 54%
“…ASD individuals who had poor social personal interaction also showed lower accuracy of facial emotion recognition, particularly in happiness and sadness emotions. These findings suggest that the altered development of emotion recognition in ASD children may be related to deficits in more complex social functions (62). Research has indicated that for TD children of about 4 years of age, their ability in recognizing happiness, sadness, and anger is maturing (16, 63).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD could indeed extract sufficient information from the eyes of others when viewing happy faces but not fearful faces (Song, Hakoda, & Sang, 2016;Song, Kawabe, Hakoda, & Du, 2012;Spezio, Adolphs, Hurley, & Piven, 2007); however, several other studies reported that individuals with ASD looked less at the eyes than control individuals, regardless of facial expressions (Corden et al, 2008;Pelphrey et al, 2002). Further, no scanning difference between ASD and TD groups for any expressions have been reported (Bal et al, 2010;De Wit, Falck-Ytter, & Hofsten, 2008;Falck-Ytter, Fernell, Gillberg, & von Hofsten, 2010;Matsuda, Minagawa, & Yamamoto, 2015). The discrepancies in previous research can be attributed to several factorsdifferent tasks (passive vs. active viewing), differing stimuli (dynamic vs. static), duration of exposure to faces, and participants' age (children vs. adults).…”
mentioning
confidence: 99%